2000
DOI: 10.1046/j.1537-2995.2000.40080924.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performances of an HTLV‐I/II EIA and other serologic and PCR assays on samples from persons at risk for HTLV‐II infection

Abstract: There were no significant differences among the sensitivities and specificities of the HTLV-I/II ELISAs (p values, 0.056-0.438). The WB and PCR assays were much more specific than the other serologic assays (p

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
4

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 61 publications
3
16
0
4
Order By: Relevance
“…These results contrast with prior reports of a relatively high rate of false-negative HTLV-1/2 EIA results in HIV-positive as well as HIV-negative populations (11,12). However, our data are in agreement with more recent reports in which no cases of "occult" HTLV-1/2 infections have been found in HTLV-1/2 EIAnonreactive individuals (3,4,7).…”
supporting
confidence: 94%
See 1 more Smart Citation
“…These results contrast with prior reports of a relatively high rate of false-negative HTLV-1/2 EIA results in HIV-positive as well as HIV-negative populations (11,12). However, our data are in agreement with more recent reports in which no cases of "occult" HTLV-1/2 infections have been found in HTLV-1/2 EIAnonreactive individuals (3,4,7).…”
supporting
confidence: 94%
“…Although we could not test HTLV-1/2 PCR in immunocompetent subjects with indeterminate HTLV WB results, results obtained in the immunosuppressed group are consistent with previous reports that have shown that PCR for HTLV-1/2 is the most sensitive and specific assay (7). Taken together, HTLV-1/2 PCR is strongly recommended for HIV-infected patients with indeterminate HTLV WB results.…”
supporting
confidence: 88%
“…The development of new EIA kits for HTLV that use recombinant proteins and synthetic peptides has increased the sensitivity and specificity of such kits, in comparison with kits that use viral lysate [25][26][27] . In contrast, the WB test for HTLV-1/2 has shown little development over recent years, and is unsuitable for blood banks because of its high costs and high proportion of indeterminate results [28][29][30][31][32] . This situation suggests that there is a need to confirm virus infection by means of molecular tests.…”
Section: Discussion Ethics Committee Approval This Study Was Approvedmentioning
confidence: 99%
“…The results indicated that WB failed to detect infection by HTLV type 2, and this was also observed in two other cases that were not included in this study. Previous studies have shown that the confirmatory sensitivity of WB for HTLV-2 is worse than for HTLV-1 and presents a greater frequency of indeterminate or false negative results [28][29][30][31] . Two (5%) out of the 40 WB-positive samples from blood donors did not present reactivity in the WB test for either of the recombinant proteins (rgp46-I or rgp46-II).…”
Section: Discussion Ethics Committee Approval This Study Was Approvedmentioning
confidence: 99%
“…However, because of the sensitivity of the assay, strict adherence to control procedures is necessary to avoid cross-contamination. The development of PCR procedures for HTLV-1 and HTLV-2 has allowed investigations to determine the prevalence and potential disease associations of HTLV-2 (1,8,26,27). In addition, PCR can be used to directly diagnose individuals with HTLV-2 infection without the need for virus isolation.…”
Section: Polymerase Chain Reaction For Detection For Htlv-2 From Cellmentioning
confidence: 99%